Adverse effects associated with bupropion therapeutic errors in adults reported to four United States Poison Centers. (4th May 2022) - Beuhler, Michael C.; Spiller, Henry A.; Alwasiyah, Dalia; Bassett, Robert; Trella, Jeanette; Huecker, Martin; Webb, Ashley N.
Abstract: Context: Bupropion is a frequently used medication. Excessive doses may cause altered mental status, seizures, and dysrhythmias. There is a need for accurate estimate of seizure risk with therapeutic errors and determination if minor symptoms are harbingers of more severe effects. Methods: A retrospective review of adult, acute, unintentional therapeutic error, single substance bupropion ingestions with known outcome reported to four poison centers from January 1, 2004 to December 31, 2016. Data included age, gender, single error dose, total bupropion dose over 18 h, prior history of seizure, management site, observation time, occurrence of an out-of-hospital adverse event, "jittery"/anxious/agitated, tachycardia/palpitations, seizures, and dysrhythmias. We recorded the total bupropion dose over 18 h if known; otherwise, we used the single error dose. We compared means for parametric data. We used Fisher's exact test and Mann–Whitney for nonparametric data. Results: We identified 754 potential cases, of which 637 met inclusion criteria after case review. Median age was 42 years, and 76.1% were female. Cases were predominantly managed at home (56.2%). Outcomes were no effect (50.1%), minor (45.5%) and moderate (4.4%). The reported dose with no effect/minor outcome was 694 (±297) mg, and for moderate outcome was 1250 (±815) mg ( p  < 0.0001). Seizures occurred in four patients with median onset time of 7 h [range 2–21.5 h]. The median reported dose in patients who seized was 900 mg [range 600–3000 mg]. Of patients who developed a seizure and/or an out-of-hospital adverse event, 83% were "jittery"/anxious/agitated whereas "jittery"/anxious/agitated was present in 27% of cases that did not ( p  = 0.008). Tachycardia/palpitations was reported in 12% of cases; more serious dysrhythmias were not reported. Conclusions: Outcomes from single unintentional ingestions of bupropion in adults are overall mild and appear to be dose related. Home management may be an option with doses up to 900 mg in an appropriate patient population.